Lessons learned from the rise and the fall of floral hemp production in Utah - Tina Sullivan; Matt Yost; Jessica Schad; Marion Murray (Agrosystems, Geosciences & Environment)
Abstract The floral hemp (Cannabis sativa L.) industry rapidly emerged in Utah in 2019 with 217 licensed growers on nearly 400 ha and has since declined annually due to market uncertainty. This scenario provided a unique opportunity to understand barriers to market entry, production challenges, and opportunities for research and education for this emerging crop. To gather information, we delivered an online survey in spring 2021 to licensed floral hemp Utah growers. Note that 85 complete responses were received by August, representing 72% of Utah counties and covering both outdoor and indoor production. Many respondents (62%) grew more than one cultivar, with Trump, Cherry Wine, and Trophy Wife being most common. Fertilizer needs were determined by plant vigor visual symptoms (14%) or crop consultants’ recommendations (16%), and often in combination with commercial lab recommendations (25%). Growers commonly reported limited fertilizer applications and those who did apply N used a rate of 10–160 kg N ha−1. Irrigation by drip was most common, with rates ranging between 279 and 508 mm (35%), and previous experience (35%) and soil moisture sensors (47%) were the most common rate determinants. Pest management responses were less focused with a wide range of reported pests. Reported production costs ranged widely from $1200 to $49,000 ha−1 with 43% of respondents not selling their harvested biomass at season end and often storing material, which required them to continue holding a license. Results indicate opportunities for improved fertilizer, irrigation, and pest management practices for hemp producers in Utah to narrow and refine product quality, production costs, and revenues.